FEMINISM IN VERONICA ROTH’S MOVIE “DIVERGENT” - Wulan Dari; Fauziah Khairina Lubis; Juli Rachmadhani Hasibuan (Universitas Negeri Medan, 2020)
The study deals with Feminism in Veronica Roth’s Movie “Divergent” from three women character. The objective of the study were to find out the types of feminism and the roles of women in Divergent movie. The research method of this study used qualitative research, relying on the analysis and description of previous researcher and the studies of feminism. The data of this study were the utterances that can be found out from the script of divergent movie. The data of this research were analyzed by using Tong’s theory. The researcher found there are 3 types of feminism in three women character in Divergent movie, they are : 5 statements that are included in liberal feminism, 12 statements are included in radical feminism, and 3 statements are included in anarchist feminism. The role of women that can be found from three women character in Divergent movie was the role of women in domestic sector and the role of women in public sector.